The impact of tolvaptan on the incidence of contrast-induced acute kidney injury and long-term prognosis in high-risk patients after coronary intervention - Chunyang Xu; Gaoliang Yan; Shenghong Ju; Yuancheng Wang; Chengchun Tang (Renal Failure)
Objective To investigate the effect of low-dose tolvaptan combined with hydration on the incidence of contrast-induced acute kidney injury (CI-AKI) and prognosis in high-risk patients undergoing coronary angiography or intervention.Methods This single-center, randomized controlled clinical trial (ChiCTR2000028834) enrolled 232 patients scheduled for elective coronary angiography or intervention, randomly assigned to the experimental group (low-dose tolvaptan + standard intravenous hydration) or the control group (standard hydration alone). Multivariate logistic regression analysis was performed to explore factors associated with CI-AKI occurrence. Kaplan-Meier survival curve was plotted with major adverse cardiovascular events (MACEs) to compare six-month survival rates between the two groups.Results The incidence of CI-AKI in the tolvaptan group was significantly lower than in the control group (10.3% vs. 23.3%, p = 0.008). Abdominal spectral CT at 24 h postoperatively showed that iodine concentration in the renal medulla was significantly lower in the tolvaptan group than in the control group (p < 0.05). The increases in creatinine and Cys-C levels and the decrease in eGFR were also significantly smaller in the tolvaptan group (p < 0.05). Multivariate logistic regression analysis indicated that tolvaptan use reduced the risk of CI-AKI (p = 0.001), while lower preoperative eGFR and higher AGEF scores were independent risk factors for CI-AKI (p < 0.05). Kaplan-Meier analysis showed no significant difference in MACEs incidence between groups over six months (93.9% vs. 88.6%, p = 0.142).Conclusion Low-dose tolvaptan combined with standard hydration reduces the incidence of CI-AKI in high-risk patients undergoing coronary intervention.Trial Registration Chinese Clinical Trial Registry (ChiCTR2000028834).